Operative Versus Nonoperative Management of Appendicitis: A Long-Term Cost Effectiveness Analysis - Lindsay A. Sceats; Seul Ku; Alanna Coughran; Britainy Barnes; Emily Grimm; Matthew Muffly; David A. Spain; Cindy Kin; Douglas K. Owens; Jeremy D. Goldhaber-Fiebert (MDM Policy & Practice, 2019)
Background. Recent clinical trials suggest that nonoperative management (NOM) of patients with acute, uncomplicated appendicitis is an acceptable alternative to surgery. However, limited data exist comparing the long-term cost-effectiveness of nonoperative treatment strategies. Design. We constructed a Markov model comparing the cost-effectiveness of three treatment strategies for uncomplicated appendicitis: 1) laparoscopic appendectomy, 2) inpatient NOM, and 3) outpatient NOM. The model assessed lifetime costs and outcomes from a third-party payer perspective. The preferred strategy was the one yielding the greatest utility without exceeding a $50,000 willingness-to-pay threshold. Results. Outpatient NOM cost $233,700 over a lifetime; laparoscopic appendectomy cost $2500 more while inpatient NOM cost $7300 more. Outpatient NOM generated 24.9270 quality-adjusted life-years (QALYs), while laparoscopic appendectomy and inpatient NOM yielded 0.0709 and 0.0005 additional QALYs, respectively. Laparoscopic appendectomy was cost-effective compared with outpatient NOM (incremental cost-effectiveness ratio $32,300 per QALY gained); inpatient NOM was dominated by laparoscopic appendectomy. In one-way sensitivity analyses, the preferred strategy changed when varying perioperative mortality, probability of appendiceal malignancy or recurrent appendicitis after NOM, probability of a complicated recurrence, and appendectomy cost. A two-way sensitivity analysis showed that the rates of NOM failure and appendicitis recurrence described in randomized trials exceeded the values required for NOM to be preferred. Limitations. There are limited NOM data to generate long-term model probabilities. Health state utilities were often drawn from single studies and may significantly influence model outcomes. Conclusion. Laparoscopic appendectomy is a cost-effective treatment for acute uncomplicated appendicitis over a lifetime time horizon. Inpatient NOM was never the preferred strategy in the scenarios considered here. These results emphasize the importance of considering long-term costs and outcomes when evaluating NOM.